Comparative Analysis of Hausa Terms and Concepts Used over Nigerian Electronic Media - Młodecki, Michał (Glottodidactica, 2005)
The study is set up to examine Hausa terms and concepts used over the Nigeria electronic media. Specifically the study analyses the use of Hausa in the eastern Hausa dialect area where we sample Plateau and Adamawa States in Nigeria. Through various instruments of research, the study comes up with various performances of the Hausa Broadcasters in terms of IOVs, IOAs, IOCs, and IOIs. The study identifies that there are various degrees of variations among Hausa Broadcasters in the use of terms and concepts in the electronic media in the non-Hausa dialect area. These variations are observed at different levels i.e. among Hausa Broadcasters in the same electronic media within the same dialect area and across electronic media. These variations occasion various degrees of performances among Hausa Broadcasters in terms of IOAs. The study further identifies various degrees of performances in terms of IOCs, which result in various degrees of performances in terms of IOIs. The performances of the Hausa Broadcasters result in confusions and breakdown of communication as reported by Hausa listeners. These variations and inconsistencies in the use of Hausa terms and concepts over the electronic media are tied up to various factors. The lack of a language monitoring body saddled with the responsibility of supervising Hausa language development in the media may be the cause of such discrepancies in the use of terms of concepts over the electronic media in the non-Hausa dialect area.